Rekonstruksi Konsep Guru Ideal dalam Tradisi Islam Klasik: Sintesis Pemikiran Al-Ghazali dan Ibn Sina serta Relevansinya bagi Kompetensi Profesional Guru PAI Kontemporer - Moh Solihin; Frenky Mubarok (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
The role of teachers in the contemporary educational ecosystem is undergoing a functional reduction due to the pressures of technical standardization, curriculum fragmentation, and accelerated digitalization. Amidst these conditions, the classical Islamic intellectual tradition offers a holistic vision of educators through the concept of murabbī, which integrates cognitive, affective, and spiritual dimensions. This article aims to analyze the concept of the ideal teacher in the thought of Al-Ghazali and Ibn Sina, map their epistemological-pedagogical convergences and divergences, and examine their relevance to the four professional competencies of contemporary Islamic Education (PAI) teachers in Indonesia. Employing a qualitative-hermeneutic approach and a comparative philosophical study, this research demonstrates that Al-Ghazali emphasizes spirituality, sincerity, moral role-modeling, and tazkiyat al-nafs (purification of the soul), whereas Ibn Sina prioritizes rationality, developmental psychology of the soul, pedagogical differentiation, and the integration of naqlī-ʿaqlī (revealed and rational) sciences. Despite differing in their epistemological foundations, both converge on the goal of holistic education (saʿādah), the rejection of the sacred-profane dichotomy, progressive approaches, and the positioning of the teacher as an agent of transformation. The synthesis of their thought is highly relevant to the pedagogical, professional, personal, and social competencies of contemporary PAI teachers. Furthermore, it offers a philosophical framework for reforming the Teacher Professional Education (PPG) curriculum, developing holistic performance assessments, and restoring the essence of the teacher as a murabbī in the Kurikulum Merdeka (Independent Curriculum) era. This article recommends integrating classical educational philosophy, developmental psychology, and professional ethics into teacher training, alongside the need for empirical research to test the effectiveness of the Ghazalian-Avicennan pedagogical model in real classroom contexts.